Serum cholinesterase combined with platelet-to-hemoglobin ratio for predicting survival prognosis in stage I-III colorectal cancer patients undergoing radical surgery: a retrospective cohort study - Luyu Huang; Kai Zhao; Hongnan Lu; Wei He; Dazhuang Miao; Yan Wang; Bingcai Li; Qi Wang; Shixiong Jiang; Yunhe Jia (BMC Gastroenterology)
Abstract Background Although surgery-based comprehensive therapy is highly effective for treating stage I–III colorectal cancer, heterogeneity in survival trajectories still exists, necessitating precise prognostic stratification. Serum cholinesterase (CHE) and the platelet-to-hemoglobin ratio (PHR) are emerging as potential prognostic markers reflecting inflammation, nutritional status, and tumor biology. This study aims to investigate their combined value in predicting survival outcomes for stage I-III CRC patients, potentially offering a cost-effective tool for personalized management. Methods The study included 673 stage I-III CRC patients who underwent radical surgery at Harbin Medical University Cancer Hospital from January to August 2019 and January to March 2020. Comprehensive clinicopathological data were collected. The patients from 2019 were used for the primary research analysis. Kaplan-Meier analysis was used for survival comparisons, while Cox regression identified independent prognostic factors. Two nomograms were developed to predict the prognosis of DFS and OS and were validated in 2020 patient cohort. Results A total of 475 patients from 2019 patient cohort were classified into three different risk groups: Group 1 (CHE ≥ 6213.3 U/L and PHR ≤ 3.03, n = 305), Group 2 (CHE < 6213.3 U/L or PHR > 3.03, n = 135), and Group 3 (CHE < 6213.3 U/L and PHR > 3.03, n = 35). Survival analysis indicated that CRC patients with low serum CHE levels and high PHR had a poorer prognosis (all p < 0.05), and the combined biomarker CHE-PHR effectively distinguished different prognostic risk groups (p < 0.001). Multivariate analysis identified Crea (p = 0.037), Eosi (p = 0.021), CA199 (p = 0.002), pTNM stage (p < 0.001), number of lymph nodes detected (p = 0.007), and CHE-PHR (p < 0.001) as independent prognostic factors for DFS, while CEA (p = 0.015), CA199 (p = 0.006), pTNM stage (p < 0.001), number of lymph nodes detected (p = 0.007), and CHE-PHR (p < 0.001) were independent prognostic factors for OS. In 2019 patient cohort t, the nomogram’s AUC values for 1-, 3-, 5-year DFS are 0.825, 0.766, and 0.748, and for 1-, 3-, 5-year OS, they are 0.787, 0.743, and 0.756. In 2020 patient cohort, the AUC values are 0.776, 0.812, 0.736 for DFS, and 0.756, 0.818, 0.789 for OS. Conclusion Lower serum CHE and higher PHR levels are linked to poorer DFS and OS outcomes. The CHE-PHR indicator serves as an independent prognostic factor for stage I-III CRC patients post-surgery, aiding in predicting recurrence and metastasis.